Germination Characteristics Associated With Glutathione S-Transferases Endowed Quizalofop-p-Ethyl Resistance in Polypogon fugax - Chen, Wen; Peng, Yajun; Lin, Qiaojiao; Zhang, Tianzhu; Yan, Bei; Bai, Lianyang; Pan, Lang (Frontiers in Plant Science, 2022)
Quantification of germination characteristics between herbicide-resistant and -susceptible weeds might provide methods to control resistant weeds and permit better prediction of evolution and persistence of herbicide resistance. This study aimed to compare the germination characteristics of Asian minor bluegrass (Polypogon fugax) populations that are resistant or susceptible to quizalofop-p-ethyl under controlled conditions, which the resistance mechanism is involved in glutathione S-transferases (GSTs) metabolism-based resistance. No major differences in seed germination were found at diverse temperatures, pH ranges, and light conditions. However, a significant difference that seed response to a gradient of osmotic and salt stress between the resistant and susceptible P. fugax populations were found. Two stress response genes (P5CS-1 and CDPK-2) in P. fugax were likely involved in germination rate as well as germination speed in response to these stresses. Subsequently, population verification demonstrated that P5CS-1 and CDPK-2 genes may be linked to the resistance mechanism. Additionally, the two genes play an important role in response to salt stress and osmotic stress as shown by transcript abundance after stress treatments. Our findings suggest that the variation of the germination characteristics in P. fugax associates with the presence of GST-endowed resistance mechanism.